STUDI KASUS : PROGRAM FISIOTERAPI PADA PASIEN DOWN SYNDROME DENGAN INTERVENSI NEURO DEVELOPMENT TREATMENT DI RUMAH SAKIT DUSTIRA - Dwi Panulat, Pandu; Rizki Prabaningtyas, Ayu; Suhartono (Yayasan Putra Sukamanah Sejahtera, 2025)
Down Syndrome is a genetic disorder in which there is an extra chromosome on chromosome 21. This extra chromosome results in excessive amounts of certain proteins, which can interfere with the body's normal growth and cause changes in brain development. This case study report aims to determine the effect of physiotherapy intervention with Neuro Developmental Treatment (NDT) on improving motor skills in Down Syndrome children. This case study report was carried out in the children's growth and development clinic at the hospital Dustira Cimahi on January 15 2024 to February 1 2024. The intervention used is Neuro Development Treatment through a stimulation and facilitation approach. The results of the Early Growth and Development Detection examination from T1 to T6 showed increased developmental achievements in aspects of fine motor skills, observation and speech. The evaluation results of the Gross Motor Functional Measurement examination showed a total score at T1: 11% and T6: 18%, there was an increase in gross motor skills of 7%. Conclusion: Intervention using Neuro Development Treatment is a therapy that has been proven to be effective in improving the motor skills of Down Syndrome children.